2020
DOI: 10.17275/per.20.26.7.2
|View full text |Cite
|
Sign up to set email alerts
|

INVITED ARTICLE: Building Journal Impact Factor Quartile into the Assessment of Academic Performance: A Case Study

Abstract: This study aims to provide information about the Q Concept defined as the division of journal impact factors into quartiles based on given field categories so that the disadvantages resulting from the direct use of journal impact factors can be eliminated. While the number of "Original articles published in the Web of Science (WoS) database-indexed journals like SCI, SSCI and A&HCI" is an important indicator for research assessment in Turkey, neither the journal impact factors nor the Q Concept of these papers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
(37 reference statements)
1
13
0
3
Order By: Relevance
“…When the literature is examined, a fair number of studies based on bibliometric analysis are observed which are of international origin (e.g. Haiqi, 1994;Moed, De Bruin & Van Leeuwen, 1995;Larson, 1996;Gupta & Pangannaya, 2000;Tonta, 2002;Al & Coştur, 2007;Wright & Pullen, 2007Atılgan, Atakan & Bulut, 2008Chen et al, 2011;Thanuskodi, 2012;Kumar, 2013;Pareek, 2013;Wang et al, 2014;Çetin & Çaylan, 2015;Kolle et al, 2015;Tupe & Khaparde , 2016;Jan, 2017;Gaviria-Marin, Merigo & Popa, 2018;Milfont et al, 2019;Karagöz & Koç Ardıç, 2019;Merigó et al, 2019;Şeref & Karagöz, 2019;Orbay, Miranda & Orbay, 2020). Although there are plentiful studies in the literature examining the field of social studies education in terms of bibliometric features, at this point, in this study, we tried to reveal the situation in terms of scientific articles and bibliometric tools related to Social Studies education.…”
Section: Introductionmentioning
confidence: 99%
“…When the literature is examined, a fair number of studies based on bibliometric analysis are observed which are of international origin (e.g. Haiqi, 1994;Moed, De Bruin & Van Leeuwen, 1995;Larson, 1996;Gupta & Pangannaya, 2000;Tonta, 2002;Al & Coştur, 2007;Wright & Pullen, 2007Atılgan, Atakan & Bulut, 2008Chen et al, 2011;Thanuskodi, 2012;Kumar, 2013;Pareek, 2013;Wang et al, 2014;Çetin & Çaylan, 2015;Kolle et al, 2015;Tupe & Khaparde , 2016;Jan, 2017;Gaviria-Marin, Merigo & Popa, 2018;Milfont et al, 2019;Karagöz & Koç Ardıç, 2019;Merigó et al, 2019;Şeref & Karagöz, 2019;Orbay, Miranda & Orbay, 2020). Although there are plentiful studies in the literature examining the field of social studies education in terms of bibliometric features, at this point, in this study, we tried to reveal the situation in terms of scientific articles and bibliometric tools related to Social Studies education.…”
Section: Introductionmentioning
confidence: 99%
“…TÜBİTAK Türkiye Adresli Uluslararası Bilimsel Yayınları Teşvik (UBYT) Programı çerçevesinde desteklenen makalelerin ortalama atıf sayısı destek almayanlara oranla biraz daha yüksektir (Tonta ve Akbulut, 2020, s. 1627. Dergi etki faktörü yüksek Q1 dergilerinde yayımlanan TR adresli makalelerin ortalama atıf sayısı daha yüksek, bu dergilerde yayımlanan ve hiç atıf almayan makalelerin oranı ise daha düşüktür (Orbay, Karamustafaoğlu ve Miranda, 2021;Orbay, Miranda ve Orbay, 2020). Ancak dünyada makalelerin yaklaşık %40'ı Q1 dergilerinde yayımlanırken, TR adresli makalelerde bu oran sadece %21'dir (Tonta ve Akbulut, 2020, s. 1627.…”
Section: Literatür Değerlendirmesiunclassified
“…Por su parte, Orbay et al (2020) presentaron un estudio sobre revistas ubicadas por cuartiles de acuerdo a las métricas aportados por WoS en el que reportaron que a pesar de la inclusión de las revistas en los núcleos principales de la indexadora (SCIE, SSCI y A&HCI) se evidencia un porcentaje de artículos que no son citados llegando a ser de hasta el 27,48% en revistas Q1 y de 48,10% en las revistas Q4. Lo anterior también ratifica que pareciera que se deben evaluar mejores metodologías de impacto donde la calidad de las publicaciones sea revisada a profundidad para Anales de Documentación, 2021, vol.…”
Section: Cuartil Actualunclassified
“…24, nº 1 ISSN electrónico: 1697-7904 --http://dx.doi.org/10.6018/analesdoc.455951. los percentiles entre 50 y 75% en el cuartil Q2 y el percentil superior (> 75%) es ocupado por las revistas Q1 (Orbay et al, 2020).…”
Section: Introductionunclassified